The Economies of Violence : The Forgotten Variable - Soto-Mayor, Guillaume, (Social Sciences E-Books Online, Collection 2025., 2025)
The covert interplay between violence and economies has long eluded public scrutiny, remaining a neglected topic in academic and policy circles alike. Amidst the proclamation of the "liberal peace", democratic nations in the 90s sidestepped discussions on violent influences within their borders. Yet, the repercussions of economic violence, spanning psychological trauma to societal upheaval, persist globally. Beyond preconceived ideas limiting violence to geographic areas and certain political regimes, identifying the profiteers and veiled beneficiaries of such systems is paramount. This understanding is crucial in dismantling the undemocratic underpinnings of economies of violence, fostering a path towards equity and peace. Contributors are Arturo Alvarado, Alain Bauer, Clotilde Champeyrache, Julien Dechanet, Nazia Hussain, David Izadifar, Louise Shelley, and Guillaume Soto-Mayor.